Survey of the Level of Knowledge and Caring Attitudes of Nurses in the Cisoka Health Center and Gembong Health Center Areas - Solikhin Romandhona (Journal of World Future Medicine, Health and Nursing, 2023)
Background Caring is a moral attitude in nursing practice. The caring nature of nurses when dealing with sick people and patient families. Nurses must show that nurses really care about patients. Nurses must be able to show empathy and be able to put themselves in the patient's position to provide quality care. Research Objectives: This study was to describe the Characteristics of the Level of Knowledge and Caring Attitudes of Nurses in the Cisoka Health Center and Gembong Health Center 2023. Research Methods This research used descriptive correlation with a cross sectional analytic design. Sampling was carried out using a total population sampling of 31 people. Data analysis used the chi-square test with the SPSS program. Research Results From the results of the statistical tabulation test using chi-square at the Cisoka Health Center, the p-value = 0.228 and the Gembong Health Center has a p-value = 0.705. The conclusion of the study of the two puskesmas showed that there was no significant relationship between nurses' knowledge and caring attitudes. cisoka health center (p = 0.228) and gembong health center (p = 0.705).